Induced Technological Change in a Multiregional, Multi-sectoral Integrated Assessment Model (WIAGEM) : Impact Assessment of Climate Policy Strategies - Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper illustrates the representation of induced technological change in the multi-regional, multi-sectoral integrated assessment model WIAGEM. The main aim of this paper is to investigate quantitatively economic impacts of climate policy measures due to induced technological changes that are considered. Improved technological innovations are triggered by increased R&D expenditures that advance energy efficiencies. Model results show that induced technological changes due to increased investment in R&D reduce compliance costs. Although R&D expenditures compete with other investment expenditures, we find that increased R&D expenditures improve energy efficiency that substantially lowers abatement costs. Without the inclusion of induced technological changes, emission targets are primarily reached by production declines, resulting in overall welfare reductions. With the inclusion of induced technological changes, emission mitigations can achieve fewer production drawbacks. Technological spill over effects also lead to improved terms of trade effects.
Keywords: C6; D5; Q4; O3; 330; Induced technological change; multi-regional applied integrated assessment model; technological spill over; Endogener technischer Fortschritt; Umwelttechnik; Energiesparen; Klimaschutz; Forschungs- und Technologiepolitik; Technologietransfer; Mehr-Länder-Modell; Mehr-Sektoren-Modell; Theorie